Need for speed: Is faster trade in the EU trade-creating? - Cecília Hornok (Magyar Nemzeti Bank, 2012)
Timely deliveries have become more important in international trade in the recent decades, mostly because of the spread of international production fragmentation. This paper provides empirical evidence on the cost of time in trade by looking at how faster trade within the European Union (EU) contributed to the trade expansion with new EU members after the enlargement in 2004. I derive a bilateral trade cost index from trade data of EU countries in 19 manufacturing industries and years 2000-2006 and perform a double difference-in-differences estimation. The results show that the enlargement-induced decline in the trade cost index, and hence trade creation, was more than twice larger in industries, where production fragmentation is typically widespread. I proxy the improvement in timeliness by the decline in the waiting time at land border crossings and estimate that saving one hour at the border is like a 0.9% trade cost decline in ad valorem terms. Robustness checks, which account for the dominant transport mode or experiment with alternative measures of timeliness, confirm the main findings.
Keywords: F13; F14; F15; 330; time cost of trade; double difference-in-differences; treatment intensity; EU enlargement